PRZYJĘCIE SPADKU Z DOBRODZIEJSTWEM INWENTARZA. OD PRAWA JUSTYNIAŃSKIEGO DO KODEKSU CYWILNEGO - Świrgoń-Skok, Renata (Zeszyty Prawnicze, 2016)
Accepting Inheritance with the Benefit of the Inventory. From Justinian Law to the Civil Code Summary The Justinian model, limiting the heir’s liability for inherited debt by means of benefit of the inventory, found a lasting place in the later private jurisprudence and received confirmation in the modern age codification of the civil law (ABGB, Napoleonic Code, BGB). Created in the Justinian code, beneficium inventarii was also adopted in the Polish succession law. It found its way to Polish legislation by way of the “great civil codes” in force in the territory of Poland in the time of partitions and after the country regained independence in 1918. Similarly, the unified and codified succession laws of Poland after World War II stipulated, beside the simple inheritance acceptance, also the acquisition of inheritance with beneficium inventarii. Other contemporary systems of legislation also apply the solutions adopted in the Roman law with regard to limiting the liability for inherited debt, e.g. Art. 7774 of French CC; § 1975 of German BGB. Both in Justinian’s legislation and in Polish laws acceptance of inheritance with the benefit of the inventory was an exception to the general rule which stipulated that the heir had unlimited liability for inherited debt. Receiving inheritance with beneficium inventarii limited the heir’s liabilities for the inherited debt in accordance with the property inventory. But in Justinian’s law the heir’s liability was based only on the inherited assets (cum viribus hereditatis) while in Polish legislation it resulted from the active value of the legacy (pro viribus hereditatis).